2021
DOI: 10.1111/tbed.14069
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of porcine circovirus type 2 infection through air and surface samples in vaccinated and unvaccinated fattening farms

Abstract: Air and surfaces of swine farms are the two alternative samples to obtain information about the health status of the herd. The aim of this study was to assess air and surface sampling for the detection of porcine circovirus type 2 (PCV2) in vaccinated and unvaccinated fattening farms, studying the relationship between the viral load in these samples with the viremia at herd level. Three swine fattening batches (one unvaccinated; two vaccinated) were monitored at 10, 12, 14, 16 and 18 weeks old; at each stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…The kidney also showed a high positive rate of PCV2, which is consistent with previous reports (Kleymann et al, 2020), and high levels of PCV can induce PDNS. In addition, the high positive rate also was revealed in immune organs such as the liver, spleen, and lymph nodes, which is associated with the frequent invasion of immune organs by PCV2 (Shi, Hou, & Liu, 2021), and viremia may occur in severe cases (Correa-Fiz et al, 2020;Lopez-Lorenzo et al, 2021). PCV2 also was detected in the intestines and stomach, which is indicative of gastrointestinal infection with circovirus, and agrees with recent reports (G. P. Liu et al, 2019;Yang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The kidney also showed a high positive rate of PCV2, which is consistent with previous reports (Kleymann et al, 2020), and high levels of PCV can induce PDNS. In addition, the high positive rate also was revealed in immune organs such as the liver, spleen, and lymph nodes, which is associated with the frequent invasion of immune organs by PCV2 (Shi, Hou, & Liu, 2021), and viremia may occur in severe cases (Correa-Fiz et al, 2020;Lopez-Lorenzo et al, 2021). PCV2 also was detected in the intestines and stomach, which is indicative of gastrointestinal infection with circovirus, and agrees with recent reports (G. P. Liu et al, 2019;Yang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…For IAV, the occurrence frequency of positive samples ranged from 0% [summer samples in Anderson et al (2016)] to 68% [calculated from Corzo et al (2013)] and the measured airborne concentration was up to 1.25×10 6 copies m -3 (Neira et al, 2016). For PCV2, positive samples ranged from 25% (López-Lorenzo et al, 2021) to 91% (Verreault et al, 2010) in occurrence frequency and from 10 3 (Rodríguez de Evgrafov et al, 2013) to 2.42×10 7 copies m -3 (López-Lorenzo et al, 2021) in airborne concentrations. For PSV, only one study was available (Naide et al, 2018) in which all bioaerosol samples were found PSVpositive and the airborne concentration ranged from 5.25×10 4 to 1.78×10 8 copies m -3 .…”
Section: Virusesmentioning
confidence: 99%
“…Because of the small volume of bioaerosol samples (and accordingly fewer viral genomic materials), airborne viral detection was less sensitive and required a greater cycle threshold (Ct) than the analysis of other samples (Refer to Section 4.4.2). However, bioaerosol measurement still showed its great potential as it yielded only slightly lower positive counts than pig oral secretion or environmental swab samples (Anderson et al, 2016;Neira et al, 2016;López-Lorenzo et al, 2021), enabled earlier viral detection than blood sample analysis (López-Lorenzo et al, 2021), and was able to reflect the onset, peak, and disappearance of a viral infection episode (Vilata et al, 2019;López-Lorenzo et al, 2021).…”
Section: Virusesmentioning
confidence: 99%
See 2 more Smart Citations